(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article problems of definition of criteria of an estimation of levels of formation of professional – pedagogical culture of the teacher of initial classes are considered. The analysis of the pedagogical literature problem of professional and pedagogical culture carried out, criteria of professional – pedagogical culture of students are determined.